NLRP3 Inflammasome and the IL-1 Pathway in Atherosclerosis. Issue 12 (8th June 2018) - Grebe, Alena; Hoss, Florian; Latz, Eicke
Abstract : Inflammation is an important driver of atherosclerosis, the underlying pathology of cardiovascular diseases. Therefore, therapeutic targeting of inflammatory pathways is suggested to improve cardiovascular outcomes in patients with cardiovascular diseases. This concept was recently proven by CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcomes Study), which demonstrated the therapeutic potential of the monoclonal IL (interleukin)-1β–neutralizing antibody canakinumab. IL-1β and other IL-1 family cytokines are important vascular and systemic inflammatory mediators, which contribute to atherogenesis. The NLRP3 (NOD [nucleotide oligomerization domain]-, LRR [leucine-rich repeat]-, and PYD [pyrin domain]-containing protein 3) inflammasome, an innate immune signaling complex, is the key mediator of IL-1 family cytokine production in atherosclerosis. NLRP3 is activated by various endogenous danger signals abundantly present in atherosclerotic lesions, such as oxidized low-density lipoprotein and cholesterol crystals. Consequently, NLRP3 inflammasome activation contributes to the vascular inflammatory response driving atherosclerosis development and progression. Here, we review the mechanisms of NLRP3 inflammasome activation and proinflammatory IL-1 family cytokine production in the context of atherosclerosis and discuss treatment possibilities in light of the positive outcomes of the CANTOS trial.